Effectiveness and Mechanisms of CdS/Porous g-C3N4 Heterostructures for Adsorption and Photocatalytic Degradation of Tetracycline Hydrochloride Wastewater in Visible Light - Ran Yan; Yuqing Mao; Meirong Zhu; Chuandong Wu; Wei Zuo; Weichen Zhu; Chenxin Zhao; Yu Tian; Jun Zhang; Jie Qiu (Applied Sciences)
In this study, CdS/porous g-C3N4 heterostructures were successfully synthesized via in situ co-precipitation to efficiently degrade tetracycline hydrochloride (TCH) under visible light. The heterostructures, particularly at a 2:1 mass ratio of CdS to porous g-C3N4, demonstrated significant improvements in both adsorption and photocatalytic performance. The adsorption and degradation rates increased 4-fold and 9.64-fold, respectively, compared to pure porous g-C3N4, with optimal removal rates achieved at a catalyst dosage of 0.2 g/L. Detailed mechanistic studies revealed that photogenerated holes (h+) and superoxide radicals (·O2−) were the primary active species driving the degradation process, while hydroxyl radicals (·OH) played a minimal role. The composite material also maintained over 70% degradation efficiency after five cycles, indicating excellent stability. This research presents a promising route for the photocatalytic treatment of wastewater containing persistent organic pollutants, offering practical insights into dosage optimization, reaction kinetics, and mechanistic pathways that enhance performance.